A numerical Study of Cubic-quartic Optical Soliton Solutions in Birefringent Fibers (European Journal of Pure and Applied Mathematics, 2025)
This study addresses the critical issue of understanding the numerical relevance of cubic-quartic solitonic expressions in birefringent fibers, a topic of increasing significance in the field of nonlinear optics due to its implications for optical communication and signal propagation. The research employs the improved Adomian decomposition scheme, developed to derive a generalized numerical method for solving complex-valued nonlinear evolution equations associated with solitons. The results demonstrate a high level of accuracy and are shown to be in total conformity with the established analytical solutions, found in the existing literature, thereby validating the effectiveness of the proposed numerical approach. Notably, the study reveals that even minor numerical errors can significantly influence the transported signal’s power, emphasizing the importance of precision in numerical methods for nonlinear systems.
Keywords: Numerical study; improved Adomian decomposition method; cubic-quartic bright solution